2016
DOI: 10.1007/s00464-016-4975-x
|View full text |Cite
|
Sign up to set email alerts
|

Standard laparoscopic versus robotic retromuscular ventral hernia repair

Abstract: RRVHR enables true AWR, with myofascial release to offset tension for midline fascial closure, and obviates the need for intraperitoneal mesh. Perioperative morbidity of RRVHR is comparable to LVHR, with shorter length of stay despite a longer operative time and extensive tissue dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 36 publications
0
62
0
5
Order By: Relevance
“…The introduction of lVHR provided several advantages over the open technique; however, this approach usually involves intraperitoneal placement of a prosthetic mesh without excision of the hernia sac or closure of the fascial defect . Failure to close the fascial defect is associated with increased seroma formation and other adverse hernia‐site outcomes . In addition, fixation of the mesh with tacs alone may increase hernia recurrence rates .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of lVHR provided several advantages over the open technique; however, this approach usually involves intraperitoneal placement of a prosthetic mesh without excision of the hernia sac or closure of the fascial defect . Failure to close the fascial defect is associated with increased seroma formation and other adverse hernia‐site outcomes . In addition, fixation of the mesh with tacs alone may increase hernia recurrence rates .…”
Section: Discussionmentioning
confidence: 99%
“…However, lVHR most often involves intraperitoneal placement of a prosthetic mesh without excision of the hernia sac or closure of the fascial defect . Failure to close the fascial defect is associated with increased seroma formation and other adverse hernia‐site outcomes . Consequently, laparoscopic techniques have been described to facilitate fascial closure, though this is often technically difficult particularly for those hernias wider than 10 cm .…”
Section: Introductionmentioning
confidence: 99%
“…In our elderly cohort, the rate of SSEs was lower than their reported rate of 15.4% for the laparoscopically treated arm. Warren et al reported that overall perioperative morbidity of RVHR is comparable to LVHR, irrespective of age. However, they also reported a statistically higher rate of SSOs after RVHR.…”
Section: Discussionmentioning
confidence: 99%
“…Although not yet scientifically proven, it may be that hernia sack resection included as a part of the method to diminish the dead space could reduce the seroma formation and possible further adverse events. The sack removal technique has been more commonly used in robotic hernia operations [27,28], where the instrumentation enables…”
Section: Discussionmentioning
confidence: 99%